2021
DOI: 10.14260/jemds/2021/247
|View full text |Cite
|
Sign up to set email alerts
|

Fipronil Poisoning Presenting as Sinus Bradycardia - A Rare Case Report

Abstract: Fipronil is an N-phenylpyrazole insecticide, a second-generation insecticide which is relatively new and now commonly used in cotton growing community of rural Central India. Farmer suicide and deliberate self-poisoning is menace to the Vidarbha region of rural Central India. There is paucity of research published on fipronil poisoning, clinical features, complications and treatment data. It is scarcely documented worldwide. Agricultural insecticides are common household items in rural areas of developing coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In this Perspective, epidemiological studies on health effect of fipronil were identified through PubMed, Web of Science, and Scopus. In total, 10 human epidemiological studies were found, including 7 acute poisoning cases and 3 chronic exposure ,, as shown in Table . Among these acute poisoning caused by fipronil exposure, all showed slight and temporary health effects in different body systems and symptoms, such as neurological, gastrointestinal, respiratory symptoms, acute kidney injury, status epilepticus anuria, etc.…”
Section: Adverse Health Effects For Humans Health?mentioning
confidence: 99%
“…In this Perspective, epidemiological studies on health effect of fipronil were identified through PubMed, Web of Science, and Scopus. In total, 10 human epidemiological studies were found, including 7 acute poisoning cases and 3 chronic exposure ,, as shown in Table . Among these acute poisoning caused by fipronil exposure, all showed slight and temporary health effects in different body systems and symptoms, such as neurological, gastrointestinal, respiratory symptoms, acute kidney injury, status epilepticus anuria, etc.…”
Section: Adverse Health Effects For Humans Health?mentioning
confidence: 99%